Insufficient sleep syndrome: An unrecognized but important clinical entity. Issue 4 (28th February 2018) - Kohyama, Jun; Anzai, Yuki; Ono, Makoto; Kishino, Ai; Tamanuki, Keita; Takada, Kazuma; Inoue, Kento; Horiuchi, Maho; Hatai, Yoshiho
Abstract: Background: A sleep clinic for adults and children was established in the Tokyo Bay Urayasu Ichikawa Medical Centre, in August 2012. Given that few sleep clinics are available in Japan specifically for children, this clinic provides the opportunity to provide data on child patients with sleep problems. Methods: Records of patients who visited the sleep clinic at the Tokyo Bay Urayasu Ichikawa Medical Centre aged ≤20 years at the first visit were retrospectively examined, along with the initial and final diagnoses. Results: Of 2, 157 patients who visited the sleep clinic at Tokyo Bay Urayasu Ichikawa Medical Centre between August 2012 and March 2017, 181 were ≤20 years old. In these 181 patients, the most frequent final diagnosis was insufficient sleep syndrome (ISS), n = 56, followed by circadian rhythm sleep–wake disorder, n = 28; insomnia, n = 28; and sleep‐related movement disorder, n = 15. Conclusions: Insufficient sleep produces various brain dysfunctions in both adults and children, and is associated with behavioral, cognitive and physical problems, as well as with atypical early development. Insufficient sleep has also been reported to cause obesity. Insufficient sleep‐induced obesity is often associated with the occurrence of metabolic syndrome. More effort is needed to ensure that children are receiving sufficient sleep.